Digital based qubit controller system for quantum computing - Khan, Kamran (Nanyang Technological University, 2022)
The science of quantum physics and its incredible phenomena serve as the foundation for the cutting-edge computing method known as quantum computing. Quantum computing is a multi-disciplinary field involving physics, mathematics, electronics, computer science and information theory. By influencing the behaviour of minute physical things, such as atoms, electrons, and photons, it outperforms classical digital computers in terms of processing power, energy consumption, and exponential speed. All quantum operations are controlled by electronic interface often operating at high temperature. These days, ready-made electronic components and devices such as an FPGA can be used to implement such an electronic interface. A direct digital synthesizer (DDS) is a digital hardware circuit that can generate analog waveforms using a fixed frequency reference clock. They are present in a wide variety of modern gadgets, including mobile phones, oscilloscope, function generators, radio, digital communication systems, GPS and many such devices. Design, analysis, optimization, synthesis, and simulation of DDS utilizing Xilinx Vivado and Cadence tools are the main topics of the dissertation. The dissertation presents several DDS architectures along with synthesis results that can help the designer choose a particular DDS depending on the application. A single spin qubit can be controlled by a digital-to-analog converter utilizing the output of a DDS module, which is a digitally coded analog signal. Fast and accurate qubit readout is essential for quantum error correction. A digitally intensive architecture with the option to change phase, frequency and type of DDS architecture is presented.